2018
DOI: 10.1007/s10461-018-2340-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Psychosocial Factors Associated with Problem Drinking Among Adults Enrolling in HIV Care in Tanzania

Abstract: Problem drinking is commonly reported among people living with HIV (PLWH), associated with suboptimal HIV care outcomes and differs by gender. Psychosocial factors associated with problem drinking among PLWH remain poorly understood, including whether they differ by gender. This analysis examines the relationship between psychosocial factors and problem drinking separately by gender among PLWH in Tanzania. Cross-sectional data were collected from 812 men and non-pregnant women living with HIV aged 18 or older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…Our findings that food insecurity was associated with alcohol misuse corroborates prior research that similarly identified links between food insecurity and alcohol use in African contexts such as Benin ( Ragetlie et al, 2021 ), South Africa ( Eaton et al, 2014 ; Dewing et al, 2013 ; Eaton et al, 2014 ), Mozambique ( Wainberg et al, 2018 ), and Tanzania ( Parcesepe et al, 2019 ). Both our qualitative and quantitative findings point to food insecurity as a stressor linked with alcohol use with urban refugee youth.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings that food insecurity was associated with alcohol misuse corroborates prior research that similarly identified links between food insecurity and alcohol use in African contexts such as Benin ( Ragetlie et al, 2021 ), South Africa ( Eaton et al, 2014 ; Dewing et al, 2013 ; Eaton et al, 2014 ), Mozambique ( Wainberg et al, 2018 ), and Tanzania ( Parcesepe et al, 2019 ). Both our qualitative and quantitative findings point to food insecurity as a stressor linked with alcohol use with urban refugee youth.…”
Section: Discussionsupporting
confidence: 89%